2011
DOI: 10.1113/jphysiol.2011.211953
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial static magnetic field stimulation of the human motor cortex

Abstract: Non-technical summary Non-invasive neuromodulation of the human brain -with pulsed magnetic fields or small direct currents -is becoming increasingly popular for treating a variety of neurological and neuropsychiatric disorders. In the present work we investigated in healthy humans the possibility of a non-invasive modulation of motor cortex excitability by the application of static magnetic fields through the scalp. We found that transcranial static magnetic field stimulation (tSMS) can reduce the excitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
187
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(206 citation statements)
references
References 24 publications
13
187
6
Order By: Relevance
“…However, rTMS and tDCS are not comfortable for subjects submitted to these techniques (Hardwick et al, 2014). Recently, transcranial static magnetic field stimulation (tSMS), a technique that is comfortable for the subject (Oliviero et al, 2011) and safe for healthy humans (Oliviero et al, 2015), was developed. With this method, stimulation is produced by placing a small neodymium magnet over the human motor cortex, which can modulate the excitability of M1 (Oliviero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rTMS and tDCS are not comfortable for subjects submitted to these techniques (Hardwick et al, 2014). Recently, transcranial static magnetic field stimulation (tSMS), a technique that is comfortable for the subject (Oliviero et al, 2011) and safe for healthy humans (Oliviero et al, 2015), was developed. With this method, stimulation is produced by placing a small neodymium magnet over the human motor cortex, which can modulate the excitability of M1 (Oliviero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transcranial static magnetic field stimulation (tSMS), a technique that is comfortable for the subject (Oliviero et al, 2011) and safe for healthy humans (Oliviero et al, 2015), was developed. With this method, stimulation is produced by placing a small neodymium magnet over the human motor cortex, which can modulate the excitability of M1 (Oliviero et al, 2011). tSMS over the motor cortex transiently inhibits motor evoked potentials (MEPs), but does not modulate the resting motor threshold (rMT) (Rosen, 2003), indicating that tSMS may not affect the membrane excitability of pyramidal neurons, but may instead induce changes at synaptic level.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for using EEG recordings to assess NIBS safety is because of the increased risk of seizures with protocols that increase cortical excitability. tSMS was shown to reduce cortical excitability both in the sensorimotor cortex of humans [2,3,24], and in the visual cortex of cats and monkeys [23]. Decreased cortical excitability should reduce rather than increase the risk of seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) are commonly used for NIBS in humans and animals. Recently we described that the application of transcranial static magnetic field stimulation (tSMS) in humans reduces the output of motor cortex -tested using TMS -for a few minutes after the end of stimulation [2]. Reduced motor output after tSMS can be explained by reduced motor cortex excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Current research has reported that the human motor cortex can be modulated by the application of static magnetic fields (SMFs) through the scalp 3) . Oliviero et al showed that 10 min of transcranial static magnetic field stimulation (tSMS) using a powerful cylindrical neodymium, iron and boron (NdFeB or "neo") magnet can reduce the amplitude of motor evoked potentials (MEPs) for a few minutes after magnet removal 3) . In addition, they demonstrated that the polarity of the SMFs was not an important factor for neuromodulation, and that tSMS was not directly associated with induced electric currents.…”
Section: Introductionmentioning
confidence: 99%